TRENDS OF VISUAL DISABILITY CERTIFICATION AT A TERTIARY CARE CENTER OF GUJARAT: A RETROSPECTIVE STUDY. - Dr Neha; Dubey, Dr . Shubhra; Vyas, Dr . Vimal J.; Parbatani, Dr . Rahil; Pandey, Dr . Ashish (Student’s Journal of Health Research Africa, 2025)
Background Visual disability is a major public health issue in India, significantly impacting individuals’ quality of life and imposing a substantial economic burden. The government has introduced the Unique Disability ID (UDID) system to provide certification and benefits for persons with disabilities, including those with visual impairments. This study aims to analyse the UDID-certified visual disability certificates issued at a tertiary care centre in Rajkot, Gujarat, to evaluate the degree, causes of visual disability, and identify any gaps in the current certification system. Methods This was a retrospective cross-sectional observational study conducted at P.D.U. Government Medical College, Rajkot, from January 2017 to December 2022. Data from 500 UDID-certified visual disability certificates, including demographic details, degree of disability, and underlying causes, were collected and analyzed. Inclusion criteria included individuals with a visual disability of 30% or higher. Statistical analysis was performed using SPSS software, and results were summarized using mean, median, and range. Results A total of 500 UDID-certified certificates were analyzed. The majority (31%) of certificates were issued in the 20–40 years age group, with a male preponderance (69.6%). The most common categories of visual disability were blindness (82%) followed by one-eyed (9.2%) and low vision (8.8%). Retinal diseases (41%), particularly retinitis pigmentosa (15.2%), were the leading causes of disability. Optic atrophy (17.8%) was the second most common cause. The study identified the under-representation of older adults and females in the certification process. Conclusions Retinal diseases, particularly retinitis pigmentosa, and optic atrophy were the most common causes of visual disability. The 20–40 years age group predominantly sought UDID certification, primarily for availing government benefits. The study highlights the need to revise the certification criteria to include individuals with less than 40% disability. Recommendation Expanding UDID certification at sub-district levels or through outreach camps to ensure broader access and inclusion.